The risk-adjusted monetary policy rule - Taisuke Nakata; Sebastian Schmidt (European Central Bank (ECB), 2016)
Macroeconomists are increasingly using nonlinear models to account for the effects of risk in the analysis of business cycles. In the monetary business cycle models widely used at central banks, an explicit recognition of risk generates a wedge between the inflation-target parameter in the monetary policy rule and the risky steady state (RSS) of inflation - the rate to which inflation will eventually converge - which can be undesirable in some practical applications. We propose a simple modification to the standard monetary policy rule to eliminate the wedge. In the proposed risk-adjusted policy rule, the intercept of the rule is modified so that the RSS of inflation equals the inflation-target parameter in the policy rule.
Keywords: E32; E52; 330; effective lower bound; inflation targeting; monetary policy rule; risk; risky steady state